Postcolonial Plumbing: Reading for Wastewater in Antjie Krog's A Change of Tongue. Issue 3 (3rd April 2022) - Lavery, Charne
Abstract : Antjie Krog's A Change of Tongue is a book about political transition, the new South Africa, and the challenges of transformation, but it is also a book about sewage. Toilets, outhouses and worms feature prominently, as do sewerage systems and wastewater treatment facilities, particularly in small towns and rural areas. Scatological themes are a staple of postcolonial fiction, constituting what has been called "excremental postcolonialism". Krog's work both underlines that vision through vivid corporeality, while also presenting plumbing as a response to the entropy of the postcolony. The first part of this essay demonstrates the ways in which the book, while explicitly concerned with land, is implicitly just as concerned with water. The second part shows how the depiction of sewage links the local and ecological to the national and continental; highlights questions of service delivery and, presciently, contemporary protest; and evokes the paradox of wastewater, between vital element and excess waste.